Parental beliefs, perceived health risks, and time investment in children - Gabriella Conti; Michele Giannola; Alessandro Toppeta (The Institute for Fiscal Studies (IFS), 2024)
When deciding how to allocate their time between different types of investment in their children, parents weigh up the perceived benefits and costs of different activities. During the COVID-19 outbreak parents had to consider a new cost dimension when making this decision: the perceived risks associated with contracting the virus. What role did beliefs about risks and returns play for the allocation of time investment in children during the pandemic? We answer this question by collecting rich data on a sample of first-time parents in England during the first lockdown, including elicitation of perceived risks and returns to different activities via hypothetical scenarios. We find that parents perceive their own time investment to be more productive and less risky than the time spent by their children in formal childcare or with peers. Using detailed time use data on children's daily activities, we show that heterogeneity in beliefs contributes to explain heterogeneity in investment choices across parents. We also document that less educated parents perceive both lower developmental returns and lower health risks from investments, while we find limited evidence of heterogeneity in preferences by socioeconomic status. This indicates that beliefs - rather than preferences - heterogeneity could contribute to inequalities in early years development, and suggests the need for timely and targeted provision of information on the actual returns and risks to different investments.
Keywords: I12; I26; J13; 330; parental beliefs; health risks; time investments; childcare; text data; coronavirus